Childfree by Choice: Competing Perspectives from Islamic Law, Indonesian Law, and Human Rights - Ilham Masri; Ismail Ismail; M. Zainal Muttaqin (Hakamain: Journal of Sharia and Law Studies, 2026)
This study aims to examine the legal status of childfree by choice in Indonesia by analyzing the competing perspectives of Islamic law, Indonesian law, and human rights, while identifying areas of convergence, divergence, and potential harmonization among these normative frameworks. The research employs a normative legal method using statutory, conceptual, comparative, and case approaches. Primary legal materials include the Qur’an, Hadith, the 1945 Constitution of the Republic of Indonesia, the Marriage Law, the Compilation of Islamic Law (KHI), international human rights instruments, and classical and contemporary Islamic legal literature, supported by scholarly publications and relevant judicial decisions. The findings demonstrate that Islamic law generally recognizes procreation as an important objective of marriage but allows contextual legal reasoning in exceptional circumstances. Indonesian law neither explicitly prohibits nor formally recognizes childfree by choice, leaving its legal status subject to interpretation within the existing legal framework. In contrast, the human rights perspective emphasizes reproductive autonomy as a fundamental right, provided its exercise remains consistent with legal obligations and the rights of others. The study concludes that the legal assessment of childfree by choice requires an integrated approach that balances religious principles, national legal norms, and human rights standards rather than relying exclusively on a single legal framework. This study contributes to contemporary Islamic family law scholarship by developing a comparative analytical framework for understanding voluntary childlessness, enriching interdisciplinary legal discourse, and providing normative references for legal reform, judicial interpretation, and public policymaking concerning emerging family issues in Indonesia.